PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE SEPAK BOLA VERBAL UNTUK MENINGKATKAN PRESTASI BELAJAR SISWAPADA POKOK BAHASAN REAKSI REDOKS DI KELAS X SMA NEGERI 1 RENGAT - Citra Amelia; Johni Azmi; Betty Holiwarni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The research about application of active learning strategy type of verbal football has been done to improve students learning achievement on the subject of redoks reactions in class X SMA Negeri 1 Rengat. Form of this research is experimental research based on pretest-posttest design. Data was taken at March 28, 2014 to May 17, 2014. The sample consisted of two classes, class XB as experiment class and class Xc as control class that randomly selected after testing homogenity. Analysis of data used t-test. The procesing of final data obtained by t-count > t-table (3,572 > 1,67). It means that the application of active learning strategy type of verbal football can improve students learning achievment on the subject of redoks reaction in class X SMA Negeri 1 Rengat where the effect of an increase is 14,88%.Keywords: Active Learning Strategy type of Verbal Football, Learning Achievement, Redoks Reaction.